Teaching English to the University Students by Using â€œWall Magazineâ€ Media as a Project Based Learning - Fitria, Tira Nur (JET ADI BUANA, 2019)
This research is to describe the implementation of Project-based Learning by using the media of wall magazine as the studentsâ€™ project in teaching English to the students of STIE AAS Surakarta. This study is descriptive qualitative research. From the result of this research, there are some steps in implementing project-based learning, they are 1) Setting the stage for students with real-life samples of the projects they will be doing. 2) Taking on the role of project designers, possibly establishing a forum for display or competition. 3) Discussing and accumulating the background information needed for their designs. 4). Negotiating the criteria for evaluating the projects. 5). Accumulating the materials necessary for the project. 6). Creating their projects. 7). Preparing to present their projects. 8). Presenting their projects. 9). Reflecting on the process and evaluating the projects based on the criteria established. By using wall magazine also bring some advantages for the students in their learning process. Project-based Learning shows the studentsâ€™ participation of their competitive work in class and gives the students opportunities to share their individual opinion and information with their group's members in order to arrange their ideas and achieve their projects. Project-based Learning creates a positive atmosphere which allows the students to be more creative in learning English